(3Cbhi ETGQI aj ebheGJ GdSHYI GdSjGQIs
(3ChdgG (B:s
(3gPg LOGhd edNUI ef GdcJH GdeWhdI , agj GdBf CbQH ETGQI ai ebheGJ GdSHYI GdSjGQI eSCdI ai eYQaI ebhe GdTeS aWQjbI Cf JCNP hSWgG hNGUJgG hJSei CjVkG HGdeQcR ddSfI GdJGeI s
(3LOGhd eQJHI Ydi GdTghQ GdYQHjIs
(3eUfhYI dYQV GdHdGO GdeUQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs